Pemodelan dan Ekperimental Performa Variasi Tekanan Kerja Injektor Mesin Diesel Induk Kapal terhadap Bentuk Semburan Nosel dan Temperatur Gas Buang Tiap Silinder - Ari Putranto, Wahyu; Khaeroman, Khaeroman; Susanto, Susanto; Nugroho, Agung (Majalah Ilmiah Gema Maritim, 2023)
The main diesel engine is a main propulsion engine that functions to move the ship. Diesel engines include the type of internal combustion engine (internal combustion engine). The combustion ignition process is carried out by spraying fuel into pressurised and high-temperature air due to compression. An injector is a device used to fog fuel. The purpose of this study is to obtain optimal parameters for the performance of the injector's working pressure. The methods used in this study are experimental and modelling. The data obtained are spray angle, length, time, and number of particles sprayed. The method used in this study is by testing injectors experimentally and simulating using CFD software. The injector input pressure parameters are 280, 300, and 320 bar while the nozzle diameter is 0.3 mm. The data obtained on the ship was then tested experimentally and simulated. In this study, there were 3 injector parameters tested. The test results of the three parameters on the injector obtained optimum data, namely at a working pressure of 320 bar nozzle diameter of 0.3 mm resulting in a spray angle of 14o, spray length of 100 mm with the fastest time of 0.00143 seconds to produce a speed of 69930.07 mm / s. The number of particles produced is 1.185071x103, so the fogging process is perfect (bursts evenly in all directions) and the temperature of the cylinder exhaust gas is 340-3600C.